Client orientation of central power generation companies. Issue 1 (3rd April 2018) - Fedosova, Alina; Volkova, Irina
Abstract : Purpose: This paper aims to identify the effects of client orientation on the business models of central power generation companies. Design/methodology/approach: Five major Russian wholesale electricity market players have been selected for the analysis conducted by applying the "business model canvas". To identify the changes induced by client orientation, the progress of companies' business models has been traced over six years, from 2009 to 2015. Findings: Five major trends in business model changes because of client orientation have been identified: declaration of the movement toward client orientation and adoption of client service standards; emergence of business diversification in favour of engineering, construction, service, operation and maintenance of power-generating facilities; increase in vertical integration; increase in the diversity of communication channels with consumers; and increase in the diversity of customer relationships. The results have been compared with those obtained from international studies. The conclusions about international and local characters of the trends are presented. Originality/value: The study contributes to the knowledge of the current and upcoming changes in the business of central power generation companies triggered by the advent of electricity prosumers. The results are valuable for both management decision makers and theorists.